Hubungan Efek Samping Obat Anti Tuberkulosis & Penyakit Penyerta dengan Kualitas Hidup Pasien Tuberkulosis Paru - Nasichah, Siti Nur Alfiyatin; Kristinawati, Beti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the relationship between side effects of anti-tuberculosis drugs (OAT), comorbidities and the quality of life of pulmonary tuberculosis patients. The research method used is quantitative with a correlative descriptive approach, data collection techniques using a cross sectional method. The results of this study showed that 53 respondents (69.7%) of pulmonary TB patients were very certain to experience side effects from Anti-Tuberculosis Drugs (OAT), 54 respondents (71.1%) of pulmonary TB patients had comorbidities and 54 respondents (71.1%) had pulmonary TB patients with Poor quality of life was 51 respondents (67.1%). In conclusion, there is a relationship between the side effects of Anti-Tuberculosis Drugs (OAT), comorbidities and the quality of life of pulmonary tuberculosis patients. Keywords: Side Effects of OAT, Quality of Life, Concomitant Diseases